bicoid RNA localization requires specific binding of an endosomal sorting complex. - Irion, U.; St Johnston, D. (Nature, 2007)
bicoid messenger RNA localizes to the anterior of the Drosophila egg, where it is translated to form a morphogen gradient of Bicoid protein that patterns the head and thorax of the embryo. Although bicoid was the first localized cytoplasmic determinant to be identified, little is known about how the mRNA is coupled to the microtubule-dependent transport pathway that targets it to the anterior, and it has been proposed that the mRNA is recognized by a complex of many redundant proteins, each of which binds to the localization element in the 3' untranslated region (UTR) with little or no specificity. Indeed, the only known RNA-binding protein that co-localizes with bicoid mRNA is Staufen, which binds non-specifically to double-stranded RNA in vitro. Here we show that mutants in all subunits of the ESCRT-II complex (VPS22, VPS25 and VPS36) abolish the final Staufen-dependent step in bicoid mRNA localization. ESCRT-II is a highly conserved component of the pathway that sorts ubiquitinated endosomal proteins into internal vesicles, and functions as a tumour-suppressor by removing activated receptors from the cytoplasm. However, the role of ESCRT-II in bicoid localization seems to be independent of endosomal sorting, because mutations in ESCRT-I and III components do not affect the targeting of bicoid mRNA. Instead, VPS36 functions by binding directly and specifically to stem-loop V of the bicoid 3' UTR through its amino-terminal GLUE domain, making it the first example of a sequence-specific RNA-binding protein that recognizes the bicoid localization signal. Furthermore, VPS36 localizes to the anterior of the oocyte in a bicoid-mRNA-dependent manner, and is required for the subsequent recruitment of Staufen to the bicoid complex. This function of ESCRT-II as an RNA-binding complex is conserved in vertebrates and may clarify some of its roles that are independent of endosomal sorting.